Spatial Conflicts Between Protected Rice Fields and Regional Spatial Planning in the Context of Sustainable Agricultural Land Protection - Radhwa, Jihan Nurfajrina; Waluyo, Waluyo (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The protection of Protected Rice Fields (LSD) serves as a strategic instrument for safeguarding national food security, as mandated by Law No. 41 of 2009 and Law No. 26 of 2007. However, its implementation is frequently hindered by inconsistencies between satellite-based LSD maps and Regional Spatial Planning (RTRW), resulting in legal uncertainty and economic losses, particularly for parties bound by contracts established prior to the policy’s enactment. This study employs a normative-juridical approach, incorporating legislative, conceptual, and case-based analyses to examine the legal framework, implementation practices, and normative–empirical gaps. The findings reveal weak synchronization between central and regional policies, the absence of derivative regional regulations, and the lack of transitional mechanisms for preexisting contracts. It concludes that effective LSD protection requires policy harmonization, integration into the RTRW, on-site verification, compensation mechanisms, and enhanced public participation to ensure fairness, legal certainty, and the sustainable use of agricultural land